International mobility programmes, European identity, and the satisfaction with EU policies - Tartaglia Stefano; Inserra Chiara (Psihologija)
In the last decades, the concept of European identity has become increasingly important in various scientific disciplines. In social sciences, several scholars have demonstrated the relationship between participation in international mobility programmes and European identity. Social interactions between people from different countries could indeed create or enhance a sense of belongingness to EU. In addition to direct contacts, ideological factors, as the political orientation, relate to identification and emotional attachment to EU. Some studies have also observed that the European identity seemed to be linked to the individual’s satisfaction with the EU action. The aim of the present research was to investigate the relationships among the participation in international mobility programmes during high school and university (Erasmus programme), European identity, and the satisfaction with EU measures during the COVID-19 pandemic. The data of the present study were collected on a sample of 516 Italian university students (62.8% females; mean age 22.7, SD=1.63) through a self-report survey online. The participation in international mobility programmes was positively related to the European social identity. Moreover, the European identity was positively related to the satisfaction with EU measures against COVID-19 pandemic and negatively related to the right-wing political orientation.